A Nanozyme with Photo‐Enhanced Dual Enzyme‐Like Activities for Deep Pancreatic Cancer Therapy. Issue 36 (2nd August 2019) - Li, Shanshan; Shang, Lu; Xu, Bolong; Wang, Shunhao; Gu, Kai; Wu, Qingyuan; Sun, Yun; Zhang, Qinghua; Yang, Hailong; Zhang, Fengrong; Gu, Lin; Zhang, Tierui; et al.
Abstract: Nanozymes have attracted extensive interest owing to their high stability, low cost and easy preparation, especially in the field of cancer therapy. However, the relatively low catalytic activity of nanozymes in the tumor microenvironment (TME) has limited their applications. Herein, we report a novel nanozyme (PtFe@Fe3 O4 ) with dual enzyme‐like activities for highly efficient tumor catalytic therapy. PtFe@Fe3 O4 shows the intrinsic photothermal effect as well as photo‐enhanced peroxidase‐like and catalase‐like activities in the acidic TME, thereby effectively killing tumor cells and overcoming the tumor hypoxia. Importantly, a possible photo‐enhanced synergistic catalytic mechanism of PtFe@Fe3 O4 was first disclosed. We believe that this work will advance the development of nanozymes in tumor catalytic therapy. Abstract : Double attack : A novel nanozyme (PtFe@Fe3 O4 ) with dual enzyme‐like activities was developed for deep pancreatic cancer catalytic therapy. The PtFe@Fe3 O4 nanozyme shows photo‐enhanced peroxidase‐like and catalase‐like activities under the acidic tumor microenvironment, as well as intrinsic photothermal effect, effectively killing tumor cells and overcoming the tumor hypoxia.